The effect of mix ingredient on compressive strength and density of oil palm shell lightweight aggregates concrete containing palm oil fuel ash as a partial cement replacement - Jubrey, Musrey (2014)
Oil palm shell (OPS) and oil palm fuel ash (POFA) is the one of the popular waste material from agro industries that can use to replace the aggregates content and cement content. This study will present some of the experimental result toward the effect of mix ingredient on compressive strength of oil palm shell lightweight aggregates concrete containing oil palm fuel ash as a partial cement replacement. Two types of mixes that its oil palm shell lightweight aggregates containing 20% of POFA and 0% POFA of oil palm shell as a control specimen was casting. The effect of superplasticizer, water cement ratio, sand content and cement content to the compressive strength and density of oil palm shell lightweight aggregates containing POFA was investigated in this study. All specimen (lOOxlOO) mm cubes was cast and subjected to water curing until the testing date. Compressive strength test was conducted following procedures in Reference standard: BS 1881: PART 116:1983 at 7 and 28days.